2013
DOI: 10.1200/jco.2012.47.0500
|View full text |Cite
|
Sign up to set email alerts
|

Second Malignant Neoplasms After Treatment of Childhood Acute Lymphoblastic Leukemia

Abstract: SMNs, except for brain tumors, AML, and MDS, have outcomes similar to their primary counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 43 publications
4
84
1
5
Order By: Relevance
“…Diese Ergebnisse unterstreichen, dass Zweitmalignome nach kST ein großes Problem darstellen [3]. Deshalb wird von allen pädiatrischen Studiengruppen versucht, die Bestrahlungsindikation möglichst restriktiv zu stellen oder sogar völlig aufzugeben.…”
Section: Kommentarunclassified
“…Diese Ergebnisse unterstreichen, dass Zweitmalignome nach kST ein großes Problem darstellen [3]. Deshalb wird von allen pädiatrischen Studiengruppen versucht, die Bestrahlungsindikation möglichst restriktiv zu stellen oder sogar völlig aufzugeben.…”
Section: Kommentarunclassified
“…Literature data indicate that around 6 to 13% of AML cases, irrespective of age, can be designated as t-AML/MDS [10,11]. In a study on 642 children who had suffered from ALL and who developed a secondary malignancy t-AML/MDS was seen in 255 children; i.e., AML in 186, MDS in 69 children [12]. After a prolonged follow-up after being cured of their primary malignancy, an increment in incidence in secondary malignancies is noted, with a total ratio of observed versus expected cases of 6603 for MDS and 226 for AML [13].…”
Section: Review Incidencementioning
confidence: 99%
“…The number of children suffering from t-AML/MDS reported in literature is very low [12,[102][103][104][105]. Tabori et al, reported on 21children with t-AML and 2 with t-MDS.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…secondary malignancies (9,10). Targeted therapies for ALL have the potential to be more effective and have fewer side effects than current treatments.…”
mentioning
confidence: 99%